Impact of unplanned peritoneal dialysis start on patients' outcomes—A multicenter cohort study - Hangai, Kellen Thayanne; Pecoits-Filho, Roberto; Blake, Peter G.; da Silva, Daniela Peruzzo; Barretti, Pasqual; de Moraes, Thyago Proença (Frontiers in Medicine, 2022)
Background: End-stage kidney disease (ESKD) patients who start unplanned dialysis therapy are more likely to be treated with hemodialysis (HD) using a central venous catheter, which has been associate with higher risk of infections and other complications, as well as with higher long-term risk of death. Urgent start PD is an alternative that have been suggested as an alternative for starting dialysis in these cases, with potentially better patient’s outcomes. However, the definition of Urgent start PD is not homogeneous and no study to our knowledge has compared clinical outcomes between urgent-start, early-start and conventional start of PD. In this study we aimed to compare these types of these types of initiation of dialysis therapy in terms of a composite outcome of patient survival and technique failure. Methods: This is a retrospective, multicentric, cohort study, involving data from 122 PD clinics of Brazil. We used the follow: Urgent Start groups refers to patients who initiated PD within 72h after the PD catheter insertion; Early Start group are those starting PD from 72 h to 2 weeks after the catheter insertion, and Conventional PD, those who used the PD catheter after 2 weeks from its insertion. We analyzed the composite endpoint of all-cause of patient’s mortality and technique failure (within the initial 90 days of PD therapy) using 3 different statistical models: multivariate Cox, Fine & Gay competing risk, and a multilevel model. Results: We included 509 patients with valid data across 68 PD clinics. There were 38 primary outcomes, comprising 25 deaths and 13 technique failures, with a total follow-up time of 1393.3 months. Urgent-start PD had no association with the composite endpoint in all 3 models. Conclusion: Unplanned PD seems to be a safe and feasible option of treatment for non-dialysis ESKD patients in urgent need of dialysis.